A Study of Millennials’s Preferences for Social Media Advertising in Delhi NCR - Arora, Taanika; Agarwal, Bhawna; Kumar, Arvind (Indian Journal of Marketing, 2018)
The growing power of the Internet has transformed the world into a small virtual place, thereby removing the geographical barriers of the world. The supremacy of the Internet has paved the way for social media advertising, which is a revolutionary change in the marketing industry. Millennials are no longer the passive recipients of information, but themselves act as a source of information by actively voicing their opinions on different social media platforms through tweets, posts, blogs,Â reviews, videos, and much more. The millennials are diverting themselves away from traditional advertisement channels and are getting engrossed in the social media platforms for being up to date with all the latest information. The stupendous impact of social media advertising on our lifestyles compelled us to explore its repercussions on millennials’s preferences. The paper attempted to examine the magnitude of social media advertising, and how different social media platforms were used by companies to influence the millennials’s preferences. The paper was based on a descriptive and inferential research design and a close ended questionnaire was used to collect primary data from social media users. The paper revealed the respondents’ preferences for using social media websites as they regularly read blogs, used social media platforms for comparison of different products, sought opinions of experts before buying a product, and the number of likes and dislikes had a significant impact on their choices. Also, the relationships between different demographic factors and social media advertising were explored, which can be effective for the marketers to frame their advertising strategies for varied target groups.